An overview on nitride and nitrogen-doped photocatalysts for energy and environmental applications. (1st September 2019) - Wang, Wenjun; Chen, Ming; Huang, Danlian; Zeng, Guangming; Zhang, Chen; Lai, Cui; Zhou, Chengyun; Yang, Yang; Cheng, Min; Hu, Liang; Xiong, Weiping; Li, Zhihao; et al.
Abstract: Semiconductor-based photocatalysis can utilize solar energy to solve the problems of energy crisis and environmental pollution. How to construct a visible-light-driven (VLD) photocatalyst was the key to efficient use of solar energy. In recent decades, nitrogen (N) resources have attained increasing interest benefit from its outstanding properties and abundant reserves. In addition, nitride and nitrogen-doped (N-doped) photocatalysts have attracted much attention owing to their unique structures, excellent physicochemical stability and low-cost. However, few reviews focus on the nitride and N-doped photocatalysts with high photocatalytic activity. Herein, the critical review summarized the recent progresses and advances in the preparation, properties and applications of nitride and N-doped photocatalysts in hydrogen evolution from water, environmental pollutants removal, carbon dioxide reduction etc. Meanwhile, the current challenges and prospects were also presented. This review aims to summarized the recent researches on nitride and N-doped photocatalysts for environmental applications and energy-related, and provide a constructive guidelines for this booming research topic. Graphical abstract: Image 1 Highlights: Nitride and nitrogen-doped photocatalysts present the promise for photocatalysis. The synthetic methods and properties of g-C3 N4 and BN are discussed. Excellent performances in energy generation and environmental purification are summarized. Current challenges and prospects of nitride photocatalysts are also presented.